Negative electrode material of transition metal element doped graphite, preparation method of negative electrode material, negative electrode and lithium ion battery

By doping the transition metal element and nitrogen element to the graphite, the problem of lithium difficulty in embedding lithium under the conditions of fast charge is solved, and the lithium storage performance and reversible capacity of lithium -ion batteries are improved.

CN119349567APending Publication Date: 2025-01-24CHONGQING INNOVATION CENTER OF BEIJING INSTITUTE OF TECHNOLOGY +1

Patent Information

Application Number
CN202411333946.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The existing graphite anode materials cannot meet the high-efficiency lithium embedded and deliquenching requirements of lithium-ion batteries under fast charging conditions, resulting in limited efficiency in the first week and difficulty in embedded lithium under large currents.

Method used

By mixing graphite with nitrogen-containing materials and heat-treating it with a source of transition metal elements in an anaerobic environment, doped transition metal elements and nitrogen element sites are formed and evenly distributed on the surface of the graphite, thereby improving the lithium storage performance of the material.

Benefits of technology

It significantly increases the embedded and dehydration rate of lithium ions, increases the reversible capacity and first effect of the material, and is suitable for fast charge applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119349567A_ABST
    Figure CN119349567A_ABST
Patent Text Reader

Abstract

The invention relates to the field of batteries, and discloses a transition metal element doped graphite negative electrode material and a preparation method thereof, a negative electrode and a lithium ion battery, and the preparation method comprises the following steps: mixing graphite and a nitrogen-containing material to obtain a graphite mixture, and carrying out heat treatment on the graphite mixture and a transition metal element source in an anaerobic environment to obtain the transition metal element doped graphite negative electrode material. The transition metal element source comprises any one of an iron source, a nickel source, a cobalt source and a manganese source, and the negative electrode material provided by the invention is relatively high in reversible specific capacity and first efficiency and has a good application prospect in the aspect of fast charging.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of batteries, and in particular to a negative electrode material of transition metal element-doped graphite, a preparation method thereof, a negative electrode and a lithium ion battery. Background Art

[0002] With the vigorous development of energy storage technology and power batteries, lithium-ion batteries are widely used. At present, graphite materials are widely available, inexpensive, and have mature preparation processes. Traditional graphite negative electrode materials have been widely used in lithium-ion battery negative electrodes. However, due to their layered structure, the small interlayer spacing is not conducive to lithium ion embedding during the lithium embedding process, resulting in limited coulomb efficiency in the first week and difficulty in lithium embedding under high current. With the development of lithium-ion battery materials, the current graphite negative electrode materials cannot meet the requirements of fast charging. Summary of the invention

[0003] The purpose of the present invention is to overcome the problem that the existing negative electrode materials cannot meet the requirements of fast charging, and to provide a negative electrode material of transition metal element doped graphite and a preparation method and a negative electrode and a lithium ion battery. The negative electrode material prepared by the present invention improves the insertion and deinsertion rate of lithium ions by doping with transition metal elements, increases the reversible capacity and initial efficiency of the material, and has good application prospects in fast charging.

[0004] In order to achieve the above object, the present invention provides, on one hand, a method for preparing a first transition metal element-doped graphite negative electrode material, wherein the preparation method comprises: mixing graphite and a nitrogen-containing material to obtain a graphite mixture, and heat-treating the graphite mixture and a transition metal element source in an anaerobic environment to obtain a negative electrode material;

[0005] Wherein, the transition metal element source includes any one of an iron source, a nickel source, a cobalt source and a manganese source.

[0006] A second aspect of the present invention provides a transition metal element doped graphite negative electrode material, wherein the negative electrode material comprises graphite, and transition metal elements and nitrogen elements doped in the graphite, wherein the transition metal element is selected from any one of iron, nickel, cobalt and manganese.

[0007] The third aspect of the present invention provides a negative electrode, which comprises the negative electrode material prepared by the preparation method described in the first aspect of the present invention or the negative electrode material described in the second aspect of the present invention.

[0008] The fourth aspect of the present invention provides a lithium ion battery, comprising the negative electrode described in the third aspect of the present invention.

[0009] When preparing the negative electrode material of transition metal element doped graphite, the present invention first mixes graphite and nitrogen-containing material, uses nitrogen as active site, and then heat treats the graphite with nitrogen active site and transition metal source under anaerobic conditions to obtain the negative electrode material of transition metal element doped graphite. That is, the present invention uses nitrogen-containing material to introduce a large amount of nitrogen element, and at the same time adds a certain amount of doping element source, and through heat treatment, the doped transition metal element and nitrogen element sites are combined and evenly distributed on the graphite surface, thereby improving the material stability and then improving the lithium storage performance of the graphite.

[0010] The preparation method provided by the present invention has simple and safe preparation process, low cost, good continuity and is suitable for mass production.

[0011] In the negative electrode material of transition metal element doped graphite provided by the present invention, the doping element includes any one of iron, nickel, cobalt, and manganese, wherein the transition metal element doping can significantly improve the conductivity, provide more lithium storage active sites, reduce the impedance of the material during the lithium insertion process, and help increase the reversible capacity of the graphite negative electrode material; further, the transition metal element can also effectively expand the interlayer spacing of the material, which is conducive to the embedding and extraction of lithium ions, and is conducive to enhancing the diffusion and insertion kinetics of lithium ions, which is beneficial to the improvement of the first effect of the graphite negative electrode. The negative electrode material of transition metal element doped graphite provided by the present invention is used as the negative electrode material of lithium ion batteries, which has good application prospects in fast charging. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 This is a schematic diagram of the appearance of the material prepared in Example 1 under a microscopic state;

[0013] Figure 2 are EDS and SEM images of the material prepared in Example 1;

[0014] Figure 3 This is a 0.1C cycle rate test diagram of Example 1;

[0015] Figure 4 This is the 1C cycle rate test chart of Example 1. DETAILED DESCRIPTION

[0016] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0017] The first aspect of the present invention provides a method for preparing a first transition metal element doped graphite negative electrode material, wherein the preparation method comprises: mixing graphite and a nitrogen-containing material to obtain a graphite mixture, and heat treating the graphite mixture and a transition metal element source in an anaerobic environment to obtain a negative electrode material;

[0018] Wherein, the transition metal element source includes any one of an iron source, a nickel source, a cobalt source and a manganese source.

[0019] When preparing the negative electrode material of transition metal element doped graphite, the present invention first mixes graphite and nitrogen-containing material, uses nitrogen as active site, and then heat treats the graphite with nitrogen active site and transition metal source under anaerobic conditions to obtain the negative electrode material of transition metal element doped graphite. That is, the present invention uses nitrogen-containing material to introduce a large amount of nitrogen element, and at the same time adds a certain amount of transition metal element doping source, and through heat treatment, the doped transition metal element and nitrogen element sites are combined and evenly distributed on the graphite surface, thereby improving the material stability and then improving the lithium storage performance of the graphite.

[0020] In some embodiments, preferably, the mass ratio of the graphite to the nitrogen-containing material is 30-100:1.

[0021] In some embodiments, preferably, the mass ratio of the graphite to the nitrogen-containing material is 50-70:1.

[0022] In some embodiments, preferably, the mass ratio of the graphite mixture to the transition metal element source is 20-100:1.

[0023] In some embodiments, preferably, the mass ratio of the graphite mixture to the transition metal element source is 50-70:1.

[0024] In the present invention, the structure and properties of the transition metal element doped graphite can be affected by controlling the amount ratio of graphite to nitrogen-containing material, the amount ratio of graphite mixture to transition metal element for doping and other parameters. The mass ratio of graphite to nitrogen-containing material can be any value between any two numbers of 30:1, 40:1, 50:1, 55:1, 60:1, 65:1, 70:1, 80:1, 90:1, 100:1. The mass ratio of graphite mixture to transition metal element source can be any value between any two numbers of 20:1, 30:1, 40:1, 50:1, 55:1, 60:1, 65:1, 70:1, 80:1, 90:1, 100:1.

[0025] In some embodiments, preferably, the particle size D of the graphite 50The particle size of graphite is 100-200 μm. Graphite particles with smaller particle size have larger specific surface area and good ion conductivity, which improves the fast charging performance of the negative electrode. The particle size of graphite can be any value between any two numbers of 100 μm, 150 μm, and 200 μm.

[0026] In some embodiments, preferably, the nitrogen-containing material is melamine and / or urea. The nitrogen-containing material has a high nitrogen content, is widely available and inexpensive, and can undergo a low-temperature decomposition reaction.

[0027] In some embodiments, preferably, the iron source includes one or more of iron carbonate, iron sulfate and ferrocene.

[0028] In some embodiments, preferably, the nickel source includes one or more of nickel carbonate, nickel sulfate, and nickelocene.

[0029] In some embodiments, preferably, the cobalt source includes one or more of cobalt carbonate, cobalt sulfate, and cobaltocene.

[0030] In some embodiments, preferably, the manganese source includes one or more of manganese carbonate, manganese sulfate, and manganocene.

[0031] The iron source, nickel source, cobalt source and manganese source mentioned above can all undergo low-temperature decomposition reactions, which is beneficial to the formation of transition metal element doping.

[0032] In some embodiments, preferably, the heat treatment temperature is 400-900° C. and the time is 1-4 hours. Parameters such as temperature and time during the heat treatment process can affect the structure and properties of the transition metal element-doped graphite.

[0033] In some embodiments, preferably, the heating rate of the heat treatment is 4-6°C / min.

[0034] The temperature of the heat treatment can be any value between any two of 400°C, 500°C, 600°C, 700°C, 800°C, and 900°C. The time can be any value between any two of 1h, 2h, 3h, and 4h. The heating rate of the heat treatment can be any value between any two of 4°C / min, 5°C / min, and 6°C / min.

[0035] In some embodiments, preferably, the mixing comprises: ball milling.

[0036] In some embodiments, preferably, the ball milling speed is 400-600 rpm, the time is 6-18 hours, and the ball to material ratio is 5-20: 1. The ball milling speed can be any value between any two of 400 rpm, 500 rpm, and 600 rpm, the time is any value between any two of 6 hours, 8 hours, 10 hours, 12 hours, 14 hours, 16 hours, and 18 hours, and the ball to material ratio is any value between any two of 5: 1, 10: 1, 15: 1, and 20: 1.

[0037] In some embodiments, preferably, the mixing further comprises: adding a solvent before the ball milling and mixing the mixture before the ball milling, and then performing the ball milling, and removing the solvent after the ball milling.

[0038] The ball milling may or may not include the addition of a solvent.

[0039] In some embodiments, preferably, after the solvent is added, the concentration of the graphite mixture is 0.1-0.3 g / mL. For a mixed method that requires the addition of a solvent and then spray drying, solvent evaporation, freeze drying and / or hydrothermal reaction, the graphite mixture after the solvent is added includes graphite, nitrogen-containing material and solvent, and its concentration can be any value between any two of 0.1 g / mL, 0.15 g / mL, 0.2 g / mL, 0.25 g / mL, and 0.3 g / mL.

[0040] In some embodiments, preferably, the method for removing the solvent comprises: one or more of spray drying, solvent evaporation, freeze drying, and hydrothermal reaction.

[0041] When the mixed method of solvent evaporation is adopted, the solvent is evaporated after mixing. The temperature of evaporating the solvent is generally 60-140°C. Evaporate until the solution becomes gelatinous, and then weigh it every 10-20 minutes. When the weight change between the two times does not exceed 0.005g, it means that the solvent is evaporated.

[0042] In some embodiments, preferably, the solvent is water and / or ethanol, and the outlet temperature of the spray drying is 60-120° C. When spray drying is used, the solvent can be water, ethanol or a mixture of the two, and there is no special requirement for the mixing ratio of the two. The outlet temperature during spray drying can be any value between any two of 60° C., 80° C., 100° C., and 120° C.

[0043] In some embodiments, preferably, the solvent is water, the freeze-drying temperature is -20°C to -10°C, and the time is 24-32 hours. When freeze-drying is used, the temperature is any value between any two of -20°C, -15°C, and -10°C, and the time can be any value between any two of 24h, 26h, 28h, 30h, and 32h.

[0044] In some embodiments, preferably, the solvent is water and / or ethanol, and the temperature of the hydrothermal reaction is 100-180°C, and the time is 6-24h. When a hydrothermal reaction is used, the solvent can be water, ethanol, or a mixture of the two. There is no special requirement for the mixing ratio of the two. Some substances will decompose during the hydrothermal reaction. Combined with subsequent heat treatment, the reversible capacity and first effect can be further improved. The hydrothermal reaction temperature is any value between any two numbers of 120°C, 140°C, 160°C, and 180°C, and the time can be any value between any two numbers of 6h, 10h, 14h, 16h, 20h, 22h, and 24h.

[0045] In some embodiments, preferably, the anaerobic environment is a vacuum environment or an inert gas environment.

[0046] In some embodiments, preferably, the vacuum degree of the vacuum environment is 500-10 Pa. The vacuum degree only needs to be anaerobic, and the vacuum degree can be any value between any two of 10 Pa, 50 Pa, 100 Pa, 150 Pa, 200 Pa, 300 Pa, 400 Pa, and 500 Pa.

[0047] In some embodiments, preferably, the inert gas of the inert gas environment includes one or more of helium, neon, argon, and krypton.

[0048] A second aspect of the present invention provides a transition metal element doped graphite negative electrode material, wherein the negative electrode material comprises graphite, and transition metal elements and nitrogen elements doped in the graphite, wherein the transition metal element is selected from any one of iron, nickel, cobalt and manganese.

[0049] In some embodiments, preferably, based on the total amount of the negative electrode material, the amount of the graphite is 90-99.5 wt %, the amount of the transition metal element is 0.1-4 wt %, and the amount of the nitrogen element is 0.5-7 wt %.

[0050] In some embodiments, preferably, based on the total amount of the negative electrode material, the amount of the graphite is 97-99 wt %, the amount of the transition metal element is 0.3-1 wt %, and the amount of the nitrogen element is 0.7-1.2 wt %.

[0051] Based on the total amount of the negative electrode material, the amount of graphite can be any value between any two of 90wt%, 91wt%, 92wt%, 93wt%, 94wt%, 95wt%, 96wt%, 97.0wt%, 97.2wt%, 97.4wt%, 97.6wt%, 97.8wt%, 98.0wt%, 98.2wt%, 98.4wt%, 98.6wt%, 98.8wt%, 99wt%, 99.2wt%, and 99.5wt%, and the amount of the transition metal element can be 0.1wt%. , 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 1wt%, 2wt%, 3wt%, 4wt%; the amount of nitrogen element can be any value between any two of 0.5wt%, 0.7wt%, 0.9wt%, 1.2%, 1.4wt%, 1.6wt%, 1.8wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, and the sum of the three is 100wt%.

[0052] In some embodiments, preferably, the particle size of the negative electrode material is 100-200 μm. The particle size of the obtained negative electrode material is mainly related to the particle size of graphite, and the particle size can be any value between any two numbers of 100 μm, 150 μm, and 200 μm.

[0053] The third aspect of the present invention provides a negative electrode, which comprises the negative electrode material prepared by the preparation method described in the first aspect of the present invention or the negative electrode material described in the second aspect of the present invention.

[0054] The fourth aspect of the present invention provides a lithium ion battery, comprising the negative electrode described in the third aspect of the present invention.

[0055] When preparing the negative electrode material of transition metal element doped graphite, the present invention first mixes graphite and nitrogen-containing material, and then heat treats the mixed graphite and transition metal element source under vacuum conditions or inert gas protection to obtain transition metal element doped graphite, that is, the present invention uses nitrogen-containing material to introduce a large amount of nitrogen element, and at the same time adds a certain amount of doping element source, through heat treatment, the doped transition metal element and nitrogen element site are combined, evenly distributed on the graphite surface, improve the material stability, and then improve the lithium storage performance of graphite. In the present invention, the structure and performance of the transition metal element doped graphite can be affected by controlling the amount ratio of graphite to nitrogen-containing material, the amount ratio of graphite to doped transition metal element, temperature, time and other parameters during heat treatment.

[0056] The preparation method provided by the present invention has simple and safe preparation process, low cost, good continuity and is suitable for mass production.

[0057] The transition metal element doped graphite negative electrode material provided by the present invention, the doping element includes any one of iron, nickel, cobalt, and manganese, wherein the transition metal element doping can significantly improve the conductivity, provide more lithium storage active sites, reduce the impedance of the material during the lithium insertion process, and help increase the reversible capacity of the graphite negative electrode material; in addition, the transition metal element can effectively expand the interlayer spacing of the material, which is conducive to the embedding and extraction of lithium ions, and is conducive to enhancing the diffusion and insertion kinetics of lithium ions, which is beneficial to the improvement of the first effect of the prepared negative electrode material. The transition metal element doped graphite provided by the present invention is used as a negative electrode material for lithium ion batteries, which has good application prospects in fast charging.

[0058] According to a particularly preferred embodiment of the present invention, a method for preparing a negative electrode material of transition metal element doped graphite, wherein the preparation method comprises: mixing graphite and a nitrogen-containing material to obtain a graphite mixture, and heat treating the graphite mixture and a transition metal element source in an anaerobic environment to obtain a negative electrode material;

[0059] Wherein, the transition metal element source includes a cobalt source and / or a manganese source;

[0060] The mass ratio of the graphite to the nitrogen-containing material is 55-65:1;

[0061] And / or, the mass ratio of the graphite mixture to the transition metal element source is 55-65:1;

[0062] The mixing includes: ball milling, adding a solvent before the ball milling and mixing before the ball milling, removing the solvent after the ball milling, and the method of removing the solvent is a hydrothermal reaction. The temperature of the hydrothermal reaction is 100-150° C. and the time is 10-15 hours.

[0063] The present invention will be described in detail below by way of examples. In the examples and comparative examples, if no specific conditions are specified, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if no manufacturer is specified, are conventional products that can be purchased commercially.

[0064] In the following examples and comparative examples, the distribution of transition metal elements was detected using a field emission scanning electron microscope (Hitachi, Japan);

[0065] The graphite content in the negative electrode material was analyzed by a thermogravimetric analyzer TGA2 (Mettler, Switzerland). The carbon content in the sample can be determined by the change in mass. The transition metal element content was tested by an inductively coupled plasma emission spectrometer (Agilent 725ES & Agilent 5110). The N element content was calculated as follows:

[0066] C N =1-C 石墨 -C 过渡金属 .

[0067] Example 1

[0068] Step (1): weighing 100 g of artificial graphite with a particle size of 150 μm and 1.67 g of melamine, mixing them with zirconium oxide ball milling beads in a ball milling jar at a ball-to-material ratio of 10:1, transferring the ball milling jar to a planetary ball mill and ball milling for 12 h at a rotation speed of 500 rpm to obtain a graphite mixture;

[0069] Step (2): Weigh 100 g of the graphite mixture and 1.67 g of ferrocene, raise the temperature to 700 ° C at 5 ° C / min in a vacuum environment with a vacuum degree of 10 Pa, and keep it warm for 3 hours to finally obtain an iron-doped negative electrode material, which is recorded as A1.

[0070] Example 2

[0071] Step (1): weighing 100 g of artificial graphite with a particle size of 150 μm and 2 g of melamine, mixing them with zirconium oxide ball milling beads in a ball milling jar at a ball-to-material ratio of 10:1, transferring the ball milling jar to a planetary ball mill and ball milling for 12 h at a rotation speed of 500 rpm to obtain a graphite mixture;

[0072] Step (2): Weigh 100 g of the graphite mixture and 2 g of ferrocene, raise the temperature to 700° C. at 4° C. / min in a vacuum environment with a vacuum degree of 10 Pa, and keep warm for 1 hour to finally obtain an iron-doped negative electrode material, which is recorded as A2.

[0073] Example 3

[0074] Step (1): weighing 100 g of artificial graphite with a particle size of 150 μm and 1.43 g of melamine, mixing them with zirconium oxide ball milling beads in a ball milling jar at a ball-to-material ratio of 10:1, transferring the ball milling jar to a planetary ball mill and ball milling for 12 h at a rotation speed of 500 rpm to obtain a graphite mixture;

[0075] Step (2): Weigh 100 g of the graphite mixture and 1.43 g of ferrocene, raise the temperature to 900° C. at 6° C. / min in a vacuum environment with a vacuum degree of 10 Pa, and keep warm for 4 hours to finally obtain an iron-doped negative electrode material, which is recorded as A3.

[0076] Example 4

[0077] Step (1): weighing 100 g of artificial graphite with a particle size of 150 μm and 3.03 g of melamine, mixing them with zirconium oxide ball milling beads in a ball milling jar at a ball-to-material ratio of 10:1, transferring the ball milling jar to a planetary ball mill and ball milling for 12 h at a rotation speed of 500 rpm to obtain a graphite mixture;

[0078] Step (2): Weigh 100 g of the graphite mixture and 5 g of ferrocene, raise the temperature to 700° C. at 5° C. / min in a vacuum environment with a vacuum degree of 10 Pa, and keep the temperature for 3 h to finally obtain an iron-doped negative electrode material, which is recorded as A4.

[0079] Example 5

[0080] Step (1): 100 g of artificial graphite with a particle size of 200 μm and 1 g of melamine were weighed, and mixed with zirconium oxide ball milling beads in a ball milling jar at a ball-to-material ratio of 10:1, and the ball milling jar was transferred to a planetary ball mill and ball milled for 12 h at a rotation speed of 500 rpm to obtain a graphite mixture;

[0081] Step (2): Weigh 100 g of the graphite mixture and 1 g of ferrocene, raise the temperature to 700° C. at 5° C. / min in a vacuum environment with a vacuum degree of 10 Pa, and keep the temperature for 3 h to finally obtain an iron-doped negative electrode material, which is recorded as A5.

[0082] Example 6

[0083] The method of Example 1 was followed, except that the particle size of the artificial graphite was 200 μm, and the artificial graphite and melamine were placed in 500 mL of ethanol at a stirring rate of 500 rpm. After stirring for 12 h, the ethanol was removed by spray drying, wherein the outlet temperature during spray drying was 90° C. The obtained negative electrode material was recorded as A6.

[0084] Example 7

[0085] The process was carried out in the manner of Example 6, except that ferrocene was replaced by nickelocene, and heat treatment was performed under an argon atmosphere. The obtained negative electrode material was denoted as A7.

[0086] Example 8

[0087] The method of Example 1 was followed, except that artificial graphite and melamine were placed in 500 mL of ethanol at a stirring rate of 500 rpm for 12 h, and then a hydrothermal reaction was carried out, wherein the hydrothermal reaction temperature was 120° C. and the reaction time was 12 h. The obtained negative electrode material was recorded as A8.

[0088] Example 9

[0089] The process was carried out in the same manner as in Example 1, except that the heat treatment temperature was 300° C. and the obtained negative electrode material was denoted as A9.

[0090] Example 10

[0091] The process was carried out in the same manner as in Example 1, except that the heat treatment temperature was 1000° C. and the obtained negative electrode material was denoted as A10.

[0092] Embodiment 11

[0093] The process was carried out in the same manner as in Example 1, except that ferrocene was replaced by cobalt sulfate, and the obtained negative electrode material was denoted as A11.

[0094] Example 12

[0095] The process was carried out in the same manner as in Example 1, except that ferrocene was replaced by manganese carbonate, and the obtained negative electrode material was denoted as A11.

[0096] Example 13

[0097] The method of Example 1 was followed, except that the mass of the artificial graphite was 100 g, the mass of the melamine was 10 g, the mass of the graphite mixture was 100 g, and the mass of the ferrocene was 10 g. The obtained negative electrode material was recorded as A13.

[0098] Embodiment 14

[0099] The method of Example 1 was followed, except that the mass of the artificial graphite was 100 g, the mass of the melamine was 0.83 g, the mass of the graphite mixture was 100 g, the mass of the ferrocene was 0.83 g, and the obtained negative electrode material was recorded as A14.

[0100] Comparative Example 1

[0101] The process was carried out in the same manner as in Example 1, except that melamine was not added. The obtained material was recorded as D1.

[0102] Comparative Example 2

[0103] The process was carried out in the same manner as in Example 1, except that ferrocene was not added, and the obtained material was recorded as D2.

[0104] Comparative Example 3

[0105] The process was carried out in the same manner as in Example 1, except that copper oxide was added and the obtained material was recorded as D3.

[0106] Comparative Example 4

[0107] The process was carried out in the same manner as in Example 1, except that zinc oxide was added and the obtained material was recorded as D4.

[0108] Comparative Example 5

[0109] The method of Example 1 is followed, except that the artificial graphite, melamine and ferrocene are ball-milled together and then heat-treated.

[0110] The appearance of the materials obtained in the above-mentioned embodiments 1-14 is not much different. Taking embodiment 1 as an example, the schematic diagram of its appearance structure under transmission is as follows: Figure 1 As shown (about 100 μm), its EDS and SEM scans are as follows Figure 2 As shown, the left picture is the EDS picture and the right picture is the SEM picture. It can be seen that the transition metal elements are evenly distributed on the graphite surface.

[0111] The materials obtained from Examples 1-14 and Comparative Examples 1-5 were tested for component content, and the results are shown in Table 1.

[0112] Table 1 Component content test results

[0113] serial number Graphite, wt% Transition metal elements, wt% N element, wt% A1 98.40 0.51 1.09 A2 98.09 0.60 1.31 A3 98.63 0.43 0.94 A4 97.13 0.91 1.96 A5 98.84 0.50 0.66 A6 98.48 0.48 1.04 A7 98.39 0.52 1.09 A8 98.56 0.45 0.99 A9 97.60 0.76 1.64 A10 98.72 0.40 0.88 A11 98.27 0.64 1.09 A12 98.11 0.80 1.09 A13 90.93 3.01 6.06 A14 99.20 0.25 0.55 D1 99.50 0.50 0.00 D2 98.90 0.00 1.10 D3 97.59 1.32 1.09 D4 97.59 1.32 1.09 D5 98.24 0.56 1.20

[0114] The materials obtained in Examples 1-14 and Comparative Examples 1-5 were assembled into lithium ion batteries and electrochemical performance tests were performed. The specific method is as follows:

[0115] (1) The materials to be tested (A1-A14 and D1-D5), the conductive agent conductive carbon black Super P, and the binder (a mixture of the binder sodium carboxymethyl cellulose CMC and the binder styrene-butadiene rubber SBR in a mass ratio of 1:1) were weighed and mixed into a slurry in a mass ratio of 8:1:0.5:0.5, and then the slurry was coated on a copper foil with a 100 μm coater, vacuum dried at 80°C, and rolled to prepare a negative electrode sheet for a lithium-ion battery;

[0116] (2) Using the prepared battery negative electrode plate, a metal lithium sheet as a counter electrode, Celgard2325 as a separator, and an electrolyte using 1 mol / L LiPF6 dissolved in a mixed solution of ethylene carbonate, dimethyl carbonate and diethyl carbonate (volume ratio of 1:1:1), 10 wt% vinylene carbonate as an additive, a CR2025 button battery was completed in an argon atmosphere glove box (H2O<0.1ppm, O2<0.1ppm).

[0117] The constant current charge and discharge test of the negative electrode material was carried out using Land CT2001A of Wuhan Landian Electronics Co., Ltd. The reversible specific capacity and coulombic efficiency of Example 1 at 0.1C were as follows: Figure 3 As shown, the reversible specific capacity and coulombic efficiency at 1C are as follows Figure 4 As shown by Figure 4It can be seen that the lithium-ion battery with the negative electrode sheet made of the negative electrode material of Example 1 has good cycle stability and capacity retention rate at high rates, indicating that transition metal element doping can effectively improve the cycle stability of the graphite negative electrode at high rates.

[0118] The test results of the embodiments and comparative examples at 0.1C and 1C are shown in Table 2 and Table 3, respectively.

[0119] Table 2 0.1C electrochemical performance test results

[0120]

[0121]

[0122] Table 3 1C electrochemical performance test results

[0123]

[0124] It can be seen from Table 2 that compared with Comparative Examples 1-5, the lithium-ion batteries containing the negative electrode sheets made of the negative electrode materials of Examples 1-14 have both higher first-cycle coulombic efficiency and capacity retention rate, indicating that transition metal element doping can effectively improve the cycle performance and reversible specific capacity of lithium-ion batteries.

[0125] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for preparing a negative electrode material of transition metal element doped graphite, characterized in that: The preparation method comprises: mixing graphite and a nitrogen-containing material to obtain a graphite mixture, and heat-treating the graphite mixture and a transition metal element source in an anaerobic environment to obtain a negative electrode material; Wherein, the transition metal element source includes any one of an iron source, a nickel source, a cobalt source and a manganese source.

2. The preparation method according to claim 1, wherein The mass ratio of the graphite to the nitrogen-containing material is 30-100:1, preferably 50-70:1; And / or, the mass ratio of the graphite mixture to the transition metal element source is 20-100:1, preferably 50-70:1; And / or, the particle size D of the graphite 50 100-200μm; And / or, the nitrogen-containing material is melamine and / or urea; And / or, the iron source includes one or more of iron carbonate, iron sulfate and ferrocene; And / or, the nickel source includes one or more of nickel carbonate, nickel sulfate, and nickelocene; And / or, the cobalt source includes one or more of cobalt carbonate, cobalt sulfate, and cobaltocene; And / or, the manganese source includes one or more of manganese carbonate, manganese sulfate, and manganocene.

3. The preparation method according to claim 1 or 2, wherein The temperature of the heat treatment is 400-900°C, the time is 1-4h, and the heating rate of the heat treatment is 4-6°C / min.

4. The preparation method according to any one of claims 1 to 3, wherein The mixing comprises: ball milling; Preferably, the ball milling speed is 400-600 rpm, the time is 6-18 hours, and the ball-to-material ratio is 5-20:

1.

5. The preparation method according to claim 4, wherein Preferably, the mixing further comprises: adding a solvent before the ball milling and mixing before the ball milling, and then performing the ball milling, and removing the solvent after the ball milling; Preferably, after adding the solvent, the concentration of the graphite mixture is 0.1-0.3 g / mL; Preferably, the method for removing the solvent comprises: one or more of spray drying, solvent evaporation, freeze drying, and hydrothermal reaction; Preferably, the solvent is water and / or ethanol, and the outlet temperature of the spray drying is 60-120°C; Preferably, the solvent is water, the freeze-drying temperature is -20°C to -10°C, and the time is 24-32h; Preferably, the solvent is water and / or ethanol, and the temperature of the hydrothermal reaction is 100-180° C. and the time is 6-24 h.

6. The preparation method according to any one of claims 1 to 5, wherein: The anaerobic environment is a vacuum environment or an inert gas environment; Preferably, the vacuum degree of the vacuum environment is 500-10Pa; Preferably, the inert gas of the inert gas environment includes one or more of helium, neon, argon and krypton.

7. A negative electrode material of transition metal element doped graphite, characterized in that: The negative electrode material includes graphite, and transition metal elements and nitrogen elements doped in the graphite, wherein the transition metal element is selected from any one of iron, nickel, cobalt and manganese.

8. The negative electrode material according to claim 7, wherein Based on the total amount of the negative electrode material, the amount of the graphite is 90-99.5wt%, the amount of the transition metal element is 0.1-4wt%, and the amount of the nitrogen element is 0.5-7wt%; And / or, the particle size of the negative electrode material is 100-200 μm; Preferably, based on the total amount of the negative electrode material, the amount of the graphite is 97-99 wt %, the amount of the transition metal element is 0.3-1 wt %, and the amount of the nitrogen element is 0.7-1.2 wt %.

9. A negative electrode, characterized in that It comprises the negative electrode material prepared by the preparation method according to any one of claims 1 to 6 or the negative electrode material according to claim 7 or 8.

10. A lithium ion battery, characterized in that: Comprising the negative electrode as claimed in claim 9.

Citation Information

Patent Citations

  • Preparation method of reduced graphene oxide loaded iron-based nanoparticle composite electrocatalytic material

    CN111715259A

  • Preparation method of lithium ion battery negative electrode material and lithium ion battery negative electrode material

    CN113130867A

  • Porous metal (iron, nickel and cobalt) doped graphite phase carbon nitride photocatalyst as well as preparation method and application thereof

    CN114797942A

  • Preparation method of high-power graphite composite material

    CN115394989A

  • Novel monatomic doped graphite negative electrode material for lithium ion battery and preparation method of novel monatomic doped graphite negative electrode material

    CN118658989A

Cited By

  • Modified graphite negative electrode active material, preparation method and application thereof, and lithium secondary battery

    CN122324802A